1998
DOI: 10.1089/hum.1998.9.14-2019
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir Chemoablation of Herpes Thymidine Kinase Suicide Gene-Modified Tumors Produces Tumor Necrosis and Induces Systemic Immune Responses

Abstract: The goal of this work was to identify potential host immune responses to thymidine kinase (TK) suicide gene-modified tumors undergoing chemoablation induced by the prodrug ganciclovir (GCV). The aims were to measure the efficacy and specificity of immunity induced against unmodified tumor, to identify qualitative or quantitative changes in the host response to TK+ tumors undergoing chemoablation that may contribute to the induction of antitumor immunity, and to compare critically the induction of immunity by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…The bystander effect is believed to be mediated partly by the transfer of phosphorylated compounds, via gap junctions, into neighboring cells, 14 ± 17 and partly by local immune responses. 1,18,19 Several studies have demonstrated the immunological component of the bystander effect. Nude mice are impaired in their ability to effect suicide gene -mediated tumor regression, 8,12 treatment generates systemic antitumor immunity, 8,20,21 and tumor regression is associated with a significant leukocytic infiltrate 11,19,22,23 and cytokine release.…”
mentioning
confidence: 99%
“…The bystander effect is believed to be mediated partly by the transfer of phosphorylated compounds, via gap junctions, into neighboring cells, 14 ± 17 and partly by local immune responses. 1,18,19 Several studies have demonstrated the immunological component of the bystander effect. Nude mice are impaired in their ability to effect suicide gene -mediated tumor regression, 8,12 treatment generates systemic antitumor immunity, 8,20,21 and tumor regression is associated with a significant leukocytic infiltrate 11,19,22,23 and cytokine release.…”
mentioning
confidence: 99%
“…Treatment of tk-or CD-transduced tumors with GCV or 5-FC in many instances produced similar antitumor immunity as immunization with radiation-or drug-treated tumor cells, 39,40 only weak or no CTL activity after prodrug treatment of tumors 37,41,42 and incomplete 29,39 or no 43,44 protective immunity. ADEPT, in contrast, generated long-lasting systemic antitumor immunity that could not be generated by immunization of radiation-treated tumor cells even with addition of immunoenzyme (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The activities of AdHSV-tk GCV could not only generate signi®cant cytotoxic activities locally and, thereby, contribute to a therapeutic response, but also potentially maximize tumor antigen presentation through its necrotic and apoptotic effects. 1,8,9 The addition of adenoviral vector-delivered locally active IL-12 could potentially maximize the in®ltration of speci®c immune cells and cause them to be activated and mature into active effectors and thus effectively co-operate with AdHSVtk GCV gene therapy. In this study we evaluated the speci®c in®ltration of immune cells within orthotopic mouse prostate cancer under single AdHSV-tk GCV or AdmIL-12 in situ gene therapy and combined treatment conditions.…”
Section: Introductionmentioning
confidence: 99%